Mathematics Textbooks with Michelin Stars (Journal of Parents and Teachers, 2018)
This article addresses the controversial issue of the use of the mathematics textbook in the classroom. Controversial because, although it is a didactic resource for teaching, it sometimes blocks the entrance of other methodologies. A series of criteria are given on what the authors consider a good textbook should be. Without rouling out that these tips could also serve publishers who, although they are eager to offer interesting and innovative products, do not always succeed.
Keywords: text books; criteria for choice; mathematics; didactic indicators; problem resolution